The Development of Individual Criminal Responsibility Under International Law: Lessons From Nuremberg and Tokyo War Crimes Trials - Adjei, William Edward (Journal of Legal Studies, 2020)
One of the most significant developments in international law was the establishment of Special Tribunals that could bring to justice individuals allegedly responsible for “grave breaches” and violations of the law against humanity. This is, undoubtedly, a recent global development that has challenged the issues of impunity and sovereignty. Since the Nazis’ atrocities and the Nuremberg trials, war crimes law has broadened its scope and has recognized a number of offenses considered as “international crimes” and which have also come to be described as “genocide”. However, although intended to put an end to the politics of impunity for the perpetrators of these crimes, a number of signatory states are reluctant to bring to justice those responsible for these defined international crimes. Indeed, the jurisprudence developed in these Special Tribunals provided an impetus for the development of the Rome Statute for the International Criminal Court (ICC). More specifically, it has been argued that war crimes and crimes against humanity are committed by men, not by abstract entities, and only by punishing individuals who commit such heinous crimes can the provisions of international law be enforced and realized. However, a perfectly reasonable case can be made that the creation of these tribunals does represent a new era in international law.